Behavior of coastal communities in dealing with microplastic pollution in salt ponds in Cirebon Regency - Astuti, Ayu Dwi; Frimawaty, Evi; Dwiyitno (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Cirebon Regency, as one of the national salt-producing centers located on the coast of the North Coast of Java is vulnerable to plastic waste pollution originating from rivers and marine debris that washes up on the beach. The purpose of this study was to analyze an assessment of the correlation between aspects of knowledge and attitudes towards the behavior of coastal communities in domestic plastic waste was also carried out to be used as a basis for preparing strategies for managing domestic plastic waste in coastal communities. Methods: The research method used is a combination of quantitative and qualitative methods consisting of a shoreline survey methodology, river waste abundance, laboratory analysis, statistical analysis, questionnaires, semi-structured interviews, and descriptive analysis. Findings: Pearson's correlation analysis showed that there was a strong (r = 0.664) and significant (0.000) positive relationship between aspects of knowledge and behavior, then aspects of attitude and behavior had a very weak positive relationship (r = 0.183) and significant (0.028). Conclusion: The community has not been pro-environmental due to the uneven distribution of available cleaning facilities. The conclusion of this study is that education, community empowerment, collaboration between village and local officials, and additional cleaning facilities are needed to reduce the problem of domestic plastic waste. Novelty/Originality of this Study: The originality of this study lies in its examination of microplastic contamination in salt ponds, directly assessing the sources of contamination from raw materials and domestic waste in Cirebon Regency, a primary salt production area in Indonesia. This focus on the direct assessment of microplastic abundance in production units, rather than commercial products, provides novel insights into the impacts of plastic pollution on food safety and local salt quality.